[223Ra] RaCl2 nanomicelles showed potent effect against osteosarcoma: targeted alpha therapy in the nanotechnology era - Yang Yang; Luciana Magalhães Rebelo Alencar; Martha Sahylí Ortega Pijeira; Beatriz da Silva Batista; Alefe Roger Silva França; Erick Rafael Dias Rates; Ruana Cardoso Lima; Sara Gemini-Piperni; Ralph Santos-Oliveira (Taylor & Francis Group, 2022)
The treatment of bone metastatsis as primary bone cancer itself is still a challenge. The use od radium dichloride ([223Ra] RaCl2) has emerged in the last few years as one of the best treatment choice for bone cancer, with especial focus in bone metastasis. The alpha-emitter radiopharmaceutical has showed potent and efficient results in several clinical trials. In this study we have formulated radium dichloride ([223Ra] RaCl2) nanomicelles in order to evaluate and compare with pure radium dichloride ([223Ra] RaCl2). The results showed that nanomicelles at the same dose had a superior effect (20% higher efficient) when compared with pure radium dichloride ([223Ra] RaCl2). The results corroborated the effectiveness of the nanosystem validating the application of nanotechnology in alpha-radiotherapy with radium dichloride ([223Ra] RaCl2).